A Sustainable Model of Social Bonding for Development of Tourism Destinations Prospecting a Case for the Indian Himalayan Region - Krishnendu Sarkar (Researchers World - International Refereed Social Sciences Journal, 2022)
Purpose: The purpose was about positing a new form of social bonding of tourists with destinations backed by social psychology theories and innovatively contributing to sustainable development. Methodology: An existing and massively successful work guarantee scheme in India was used as a reference for a simulated modeling system development for empowering the demanding people in destinations with the learning of English, Science, Technology, Entrepreneurship, Entertainment, and Management (ESTEEM) from tourists or visitors. Its qualitative design was based on a mix of ethnography, phenomenology, and several studies in the context of the tourism-attractive Indian Himalayan region, as case. Findings: The Model was not in any conflict with the tourism business. Instead, it offered rewards to tourists or visitors under ESTEEM sectors of work linked with the sustainable development goals. The findings at the pilot level considered 180 days of ESTEEM tourism with the absorption of ESTEEM services from 20 percent of total tourists in a select cluster of popular yet vulnerable destinations in the Indian Himalayan Region. Then, by multi-objective optimization of maximum stay days, maximum rewards, and minimum cost, involving 2 work sectors of Health and Education, the per capita cost of USD 3.5 was estimated for about 8 million beneficiaries. Implications: Finally, the Model was able to maintain its hypotheses around a unique form of social bonding for desired change and local development, that can be posited not only for the revival of tourism business, particularly after its damages caused by the Coronavirus pandemic and in general open new possibilities around strengthening societies. Originality: Thereby, instrumenting a novel approach for modeling sustainable development of destinations under the sustainable development goals 2030, leveraging on the human agencies under the massive tourism system.